Recent Innovations in AI Privacy: Protecting Data in the Age of Machine Learning - Siddhant Sonkar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores recent advancements in privacy-preserving technologies within artificial intelligence systems, focusing on five key approaches: federated learning, differential privacy, homomorphic encryption, privacy-preserving machine learning (PPML), and zero-knowledge proofs. The article examines how these technologies address critical privacy challenges in machine learning environments while maintaining model performance and utility. The article highlights the implementation of these approaches across various domains, particularly in healthcare and financial services, demonstrating their effectiveness in protecting sensitive data throughout the machine learning lifecycle. The article reveals how these technologies complement each other to create robust privacy protection frameworks while enabling organizations to leverage the power of AI without compromising data confidentiality.
Keywords: Privacy-Preserving AI; Federated Learning; Differential Privacy; Homomorphic Encryption; Zero-Knowledge Proofs